2000
DOI: 10.1103/physrevlett.85.1250
|View full text |Cite
|
Sign up to set email alerts
|

Melting of Isolated Tin Nanoparticles

Abstract: The melting of isolated neutral tin cluster distributions with mean sizes of about 500 atoms has been investigated in a molecular beam experiment by calorimetrically measuring the clusters' formation energies as a function of their internal temperature. For this purpose the possibility to adjust the temperature of the clusters' internal degrees of freedom by means of the temperature of the cluster source's nozzle was exploited. The melting point of the investigated tin clusters was found to be lowered by 125 K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
135
0
4

Year Published

2002
2002
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(149 citation statements)
references
References 16 publications
10
135
0
4
Order By: Relevance
“…For overheating, z ib c i ÿm > 1 and b < 1. Therefore, the models of RMSD instability, LSN, LNG, surface-phonon instability, and the current [317,318], Sn 10e19 [322], Sn 19e31 [266], Ga þ 39e40 [317], Sn 500 [333], and Sn nanosolid on Si 3 N 4 substrate [289]. The T m deviation of Al þ 50e60 clusters [334] from the predictions indicates that the bond nature alteration of Al is less significant compared to Sn and Ga bonds.…”
Section: Remarksmentioning
confidence: 99%
“…For overheating, z ib c i ÿm > 1 and b < 1. Therefore, the models of RMSD instability, LSN, LNG, surface-phonon instability, and the current [317,318], Sn 10e19 [322], Sn 19e31 [266], Ga þ 39e40 [317], Sn 500 [333], and Sn nanosolid on Si 3 N 4 substrate [289]. The T m deviation of Al þ 50e60 clusters [334] from the predictions indicates that the bond nature alteration of Al is less significant compared to Sn and Ga bonds.…”
Section: Remarksmentioning
confidence: 99%
“…One of these points is the existence of surface melting, i.e., a coexistence of a liquid-like layer of atoms at the surface with the solid core material at temperatures below the respective melting point. 6,7 While this effect seems to be very basic, there is still a lack of unambiguous experimental proof regarding the details, in particular for gold nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…One of these points is the existence of surface melting, i.e., a coexistence of a liquid-like layer of atoms at the surface with the solid core material at temperatures below the respective melting point. 6,7 While this effect seems to be very basic, there is still a lack of unambiguous experimental proof regarding the details, in particular for gold nanoparticles.Inasawa et al 8 have tried to investigate the shape transformation of elongated particles on a surface induced by static heating (ex situ) and concluded that a transformation into spheres takes places at temperatures as low as 400°C. A similar, very recent study has shown that nanorods with a large aspect ratio of the axes can be transformed at 200°C into spheres and partial relaxation occurs much earlier (100°C).…”
mentioning
confidence: 99%
“…[5][6][7][11][12][13] Experimental evidence of the decrease in T m has been demonstrated by a variety of techniques. 2,[14][15][16][17][18] In addition, the influence of surrounding matrix on T m has been demonstrated, e.g., in our previous work. 19 However, the influence of the interaction between the metal nanoparticles ͑or filling factor of nanocomposite͒ on their melting point is an unstudied problem.…”
Section: Introductionmentioning
confidence: 99%